Pengaruh Beauty Influencer, Harga Kompetitif, dan Kualitas Hubungan Pelanggan Terhadap Loyalitas Pengguna Jasa Makeup Artist Pada Remaja Putri di Kota Pontianak - Natalia Vania Tjandra; Dewi Santika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to determine the influence of beauty influencers, competitive pricing, and relationship quality on the loyalty of teenage girls in Pontianak City who use makeup artist services. The study population includes all teenage girls in Pontianak City who have ever used makeup artist services, although the exact number is unknown. A total of 113 respondents participated in the study, using a purposive sampling method. Data collection was conducted through the distribution of questionnaires, and data analysis was processed using SPSS version 26. The results indicate that beauty influencers do not have a significant effect on consumer loyalty, suggesting that promotions via beauty influencers have not yet become a primary factor in maintaining loyalty among users of makeup artist services. Conversely, competitive pricing and the quality of customer relationships were found to have a positive and significant effect on consumer loyalty, meaning that the more appropriate the price and the better the relationship established with the customer, the higher the tendency for consumers to continue using the service. These findings confirm that price and customer relationship factors play a more dominant role in shaping loyalty compared to beauty influencers.